Gender in Academic Networking: The Role of Gatekeepers in Professorial Recruitment. (4th December 2013) - van den, Marieke; Benschop, Yvonne
Abstract The aim of this study is to build a theoretical framework to understand how gendered networking practices produce or counter inequalities in organizations. We introduce a practice approach combined with a feminist perspective in organization network studies. The notions of gender and networking as social practices allow better insights into what people say and do in networks, and the ways that networking produces or counters gender inequalities. We draw on empirical material about professorial appointments in Dutch academia and analyse the accounts of gatekeepers illuminating their networking practices. The accounts show which networking practices gatekeepers routinely use in recruitment and how these networking practices are intertwined with gender practices. We use the notion of mobilizing masculinities to understand the self‐evident identification of men gatekeepers with men in their networks, and to understand how both men and women gatekeepers prefer the male candidates that resemble the proven masculine success model. Furthermore, this study provides the first empirical insights in mobilizing femininities in which women search for and support women candidates. We show how the gender practice of mobilizing femininities is a more precarious and marked practice than mobilizing masculinities. Mobilizing femininities in networking is intended to counter gender inequalities, but is only partially successful. Through constructions of 'who you can trust' or 'who is a risk', gatekeepers exercise the power of inclusion and exclusion and contribute to the persistence of structural gender inequalities.